The Neotropical annual killifish genus Pterolebias Garman (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology, and taxonomic revision - Costa, Wilson J.e.m. (Zootaxa, 2005)
Pterolebias is revised on the basis of osteology, external morphology, latero-sensory system, and color patterns. Two species are recognized as valid: P. longipinnis, from the eastern and southern Amazon River basin and the ParanáParaguay River system, in Brazil, Bolivia, Paraguay and Argentina; and P. phasianus, from the Paraguay River basin, in Brazil and Bolivia. Pterolebias bokermanni and P. luelingi are considered synonyms of P. longipinnis. Monophyly of Pterolebias is corroborated by the morphology of the angulo-articular, second pharyngobranchial, maxilla, metapterygoid, quadrate, basihyal, and two derived color patterns. In contrast to molecular studies, monophyly of an assemblage including Pterolebias and Gnatholebias is herein strongly supported by reduction of the interarcual cartilage, morphology of the anterior proximal radials of the anal fin and pelvic girdle, presence of scale rows on the anal-fin base, derived jaw dentition, numerous pelvic-fin rays, and long pelvic fins. A recent proposal to unite Pterolebias and Gnatholebias in a single genus is rejected.